PENGARUH PENGAWASAN DISIPLIN KERJA DAN KOMPENSASI TERHADAP EFEKTIVITAS KERJA PENGAWAI DINAS TATA RUANG KABUPATEN TANA TORAJA - Christian Parady (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
An observation system is Effective, when that observation system influence the flexibility principle, the core important in discipline work all employees, mirroring that function - other human resource management function have been executed by according to plan by paying attention to policy in determining compensation influenced by big size measure minimize the company nya which comparison of wage rate need in paying attention to For example : Storey; Level of Education and year of service